BREAST FEEDING PRACTICES AND HEALTH OF INFANTS - *Seema Devi Kanchan Kulshrestha (International Journal of Research Science and Management, 2016)
In India nearly 60 infants per thousand live-births do not live long enough to see their first birthday and almost another six die before they reach their fifth birth day. The major causes of deaths of these children are malnutrition and infections. The children under five are prone to infections due to lack of awareness about feeding practices especially breastfeeding. It is well known that breastfeeding practices can have a substantial effect on infant health and mortality in developing countries. There are at least three known mechanisms by which breastfeeding contributes to infant health and survival. First, breast milk is ideally suited to the baby’s metabolic structure and contains the optimal combination of nutrients. Second, breastfeeding allows the mother to pass on immunities that she herself has acquired to the baby. Education is a statistically significant variable that explains the nutritional status of the infants. It has been found to have a strong association with breast-feeding and feeding of colostrums. Educated mothers start supplementary feeding to the children at the appropriate age reduces the chances of malnutrition among children.